CSS Quick Syntax Reference - Olsson, Mikael (Apress : Imprint: Apress, 2014)
The CSS Quick Syntax Reference is a 150-page syntax reference to the Cascading Style Sheet specification and style sheet language. It presents the essentials of CSS in a well-organized format that can be used as a handy reference. You won't find any technical jargon, bloated samples, drawn out history lessons or witty stories in this book. What you will find is a CSS reference that is concise, to the point, and highly accessible. The book is packed with useful information and is a must-have for any CSS programmer or Web developer. In the CSS Quick Syntax Reference, you will find: A concise reference to CSS Short, simple, and focused code examples for presentation semantics A well laid out table of contents and a comprehensive index allowing easy review.